The identity of Zachaenus roseus Cope, 1890 (Anura: species inquirenda) - Lavilla, Esteban Orlando (2010)
Zachaenus roseus Cope, 1890, has puzzled systematists working in southern South America. A single individual, the holotype, has ever been collected and this specimen is in extremely poor preservation condition. Herein, the precise location of the type locality of Z. roseus is determined based on a historical review of the literature. Furthermore, following a careful comparison with all species that inhabit the southern austral forest, and that could potentially correspond to Zachaenus roseus, we conclude that this taxon is placed in the synonym of Eupsophus calcaratus (Günther, 1881).